Control of Plant-parasitic Nematode by Incorporation of Deoiled Cakes of Tree Seeds on Su-babul, Leucaena leucocephala (lam.) De Wit. - Azmi, Mujib I. (Indian Forester, 1990)
Experiment was conducted to evaluate the effect of deoiled cakes of tree seeds i.e. neem, caster and mahua on the population of plant-parasitic nematodes on su-babul seedlings. Significant reduction in the populations of plant-parasitic nematodes were recorded from 40-66% and corresponding increase in length and dry weight of seedling (24-40%) were observed. Highest reduction in the population of plant parasitic nematodes (66%) and maximum increase in length and dry weight of seedling (40%) were achieved by incorporating neem cake @ 3% w/w in soil.